Contraceptive Options Following Gestational Diabetes: Current Perspectives - Turner, Ashley M (Open Access J Contracept, 2019)
Gestational diabetes mellitus (GDM) complicates approximately 7% of pregnancies in the United States. Along with risk factors related to pregnancy, women with a history of GDM also have an increased risk of developing type 2 diabetes mellitus later in life. These women require special consideration when discussing contraception and other reproductive health issues. GDM carries a category 1 rating in the US Medical Eligibility Criteria for all contraceptive methods, which supports safety of the various methods but does not account for effectiveness. Contraceptive options differ in composition and mechanisms of action, and concerns have been raised about possible effects of contraception on metabolism. Clinical evidence is limited to suggest that hormonal contraception has significantly adverse effects on body weight, lipid, or glucose metabolism. In addition, the majority of evidence does not suggest a relationship between development of type 2 diabetes mellitus and use of hormonal contraception. Data are limited, so it is challenging to make a broad, general recommendation regarding contraception for women with a history of GDM. A woman’s history of GDM should be considered during contraceptive counseling. Discussion should focus on potential medical comorbidities and the implications of GDM on future health, with special consideration of issues including bone health, obesity, cardiovascular disease, and thrombosis risk. Providers must emphasize the importance of reliable, highly effective contraception for women with GDM, to optimize the timing of future pregnancies. This approach to comprehensive counseling will guide optimal decision-making on contraceptive use, lifestyle changes, and planning of subsequent pregnancies.